Monkeys can associate visual stimuli with reward delayed by 1 s even after perirhinal cortex ablation, uncinate fascicle section or amygdalectomy. - Gutnikov, SA; Ma, Y; Buckley, M; Gaffan, D (1997)
In the present experiment monkeys learned concurrent associations of two-dimensional objects (presented on a computer screen) with delayed reward. Hypothetical mechanisms of associative memory, such as long-term potentiation (LTP), required coincidental activation of two population of neurons: one representing the object and the other signalling the reward. In monkeys neurons in area TE of temporal cortex show object-specific activity during object presentation but only fraction of those neurons remain active after stimulus offset. In a delayed reward condition the majority of object-specific neurons in TE cease firing before reward is given and can be detected. In the present study the rate of learning with 1000 ms delay of reward was no slower than learning with immediate reward. This indicates that information about the object is somehow retained across the delay, possibly somewhere outside TE. In the present study we tested that assumption. Area TE projects to the perirhinal cortex and, via uncinate fascicle, to the prefrontal cortex. In our hands, ablations of perirhinal cortex or disconnection of prefrontal cortex from TE (by transection of uncinate fascicle) did not impair learning with delayed reward. Ablation of amygdala, a structure involved in reward-learning, slowed down learning equally with and without delay. We conclude that retaining information about the visually perceived objects across a delay does not exclusively depend upon integrity of perirhinal cortex, or uncinate fascicle, or amygdala. Parallel involvement of those structures remains a possibility and establishment of the role of residual activity of TE neurons requires further neurophysiological investigation.